Factors causing fewer female students in Binga district to proceed from grade seven to advanced level - Maposa, Obert (Midlands State University, 2018)
The research study sort to find out the factors affecting girls from proceeding in their large numbers to advanced levels of secondary education. The qualitative research design grounded in the interpretivist paradigm was used in this study. Data generating instruments were semi-structured interviews and document analysis guides. The sample of two school heads, six teachers, eight pupils, four parents and four young ladies were selected as respondents. The generated data was analysed using thematic approach. The factors that cause fewer female students in advanced levels were the early marriages and unplanned pregnancies, poverty, lack of parental financial support, religious teachings and gathering that disturb girls’ education. It is recommended that parents should fully support the education of girls as they do to their sons, teachers should intensify counselling and career guidance sessions in schools to equip girls and finally both parents and school authorities must report cases of child abuse to reduce school drop outs.